Analgesic drug delivery via recombinant tissue plasminogen activator and microRNA-183-triggered opening of the blood-nerve barrier. (March 2016) - Yang, Shaobing; Krug, Susanne M.; Heitmann, Johanna; Hu, Liu; Reinhold, Ann Kristin; Sauer, Solange; Bosten, Judith; Sommer, Claudia; Fromm, Michael; Brack, Alexander; Rittner, Heike L.
Abstract: The peripheral nerve contains three barriers which include the blood-nerve barrier consisting of endoneurial vessels and the perineurium as well as autotypic junctions in Schwann cells. The perineurium prevents diffusion of perineurally injected drugs that can be used for selective regional pain control. It is composed of a basal membrane and layers of perineurial cells sealed by tight junction proteins like claudin-1. Claudin-1 expression and barrier function are regulated via low-density lipoprotein receptor-related protein (LRP-1). Perisciatic application of recombinant tissue plasminogen activator (rtPA) or the catalytically inactive rtPAi – both agonists of LRP-1 – reduced claudin-1 mRNA and protein expression in the rat nerve. This facilitated an increase of nociceptive thresholds after local application of hydrophilic opioids or the voltage gated sodium channel blocker (NaV 1.7) ProToxin-II without apparent nerve toxicity. RtPA-induced barrier opening was mediated by LRP-1 and intracellularly by Erk phosphorylation. In silico, microRNA (miR)-rno-29b-2-5p and rno-miR-183-5p were identified as potential regulators of claudin-1 transcription in the rat. RtPA application increased miR-183-5p in the sciatic nerve. MiR-183-5p mimics functionally opened the perineurium and downregulated claudin-1 expression in vivo . In vitro, hsa-miR-183-3p mimics reduced claudin-1 expression in human HT-29/B6 cells. Overall, rtPA regulates perineurial barrier tightness via LRP-1, Erk phosphorylation and miR-183-5p/3p. This mechanism might serve as a new principle to facilitate drug delivery to peripheral nerves in humans.